Surse ale atitudinilor politice în România postrevoluţionară - Zamfir, Cătălin (Calitatea Vieții, 1992)
Based on the data of two field researches, the paper approaches the topic concerning the sources of the political attitudes. Besides the ideological options explaining the differences of attitudes in front of different elements of the political system, the paper spotlights also the contribution of some special social and psychological factors.